Expression of miRNA and Occurrence of Distant Metastases in Patients with Hürthle Cell Carcinoma - Rok Petric; Barbara Gazic; Katja Goricar; Vita Dolzan; Radan Dzodic; Nikola Besic (International Journal of Endocrinology)
Background. Hürthle cell thyroid carcinoma (HCTC) is a rare type of thyroid carcinoma. In the present study, we investigated whether the expression of miRNAs of interest is associated with the occurrence of metastases in patients with HCTC. Materials and Methods. In 39 patients with HCTC (22 with nonmetastatic and 17 with regional or distant metastatic disease), the expression levels of six miRNAs (miR-138, miR-183, miR-221, miR-222, miR-768-3p, and miR-885-5p) and U6 snRNA as endogenous control were determined in FFPE samples of primary tumor and normal thyroid tissue using TaqMan miRNA assays. Results. In patients with HCTC, miR-138 and miR-768-3p were downregulated in tumor samples compared to normal tissue (p=0.013 and p=0.010, resp.). These two miRNAs were also significantly downregulated in tumor samples of patients with metastatic disease (p=0.030 and p=0.048, resp.) but not in patients with nonmetastatic disease (p=0.249 and p=0.101, resp.). In patients with nonmetastatic disease, miR-221 and miR-885-5p were slightly, albeit significantly, upregulated in tumorous compared to normal tissue (p=0.042 and p=0.027, resp.). Conclusion. Expression of miRNA (miR-183, miR-221, and miR-885-5p) in tumor tissue is associated with the occurrence of distant metastases in patients with HCTC.